ISMUBA Curriculum Development at SMP Muh Muntilan - Hardian, Rafik Tri (Universitas Muhammadiyah Surakarta, 2023)
This study is related to ISMUBA curriculum development. Referring to the background of the problems faced in education in the era of technology and globalization which are developing rapidly, the curriculum in education is very important to start an effective, efficient and creative learning process. The aim of this research is to find out, ISMUBA curriculum development in the learning process. This type of research is Field Research with a qualitative strategy. Data processing techniques using observation, interviews and documentation. Data analysis was carried out by data reduction, reduction, and data processing according to the research objectives. Based on the results of the research, the use of the curriculum at SMP Muh Muntilan uses the ISMUBA curriculum from the Muhammadiyah Central Leadership Council. Development is carried out in two ways, namely in the ISMUBA Practice Project school, Student Assessment Pause Contest, Hisbul Wathon, Tapak Suci, Dzuhur and Azar Prayer Worship Activities, and Gitarmu (Enterprising Ramadhan SMPMuh Muntilan) and outside of school such as the application of Worship Practices that have been taught (Fardhu Prayers, Sunaah Prayers, Funeral Prayers and Thaharah), Koran at each other's homes, visiting sick people, distribution of sacrificial animals and competitions outside of school as well as activities that support the ISMUBA education program. But the inhibiting factors in the curriculum require teacher evaluation and textbook facilities to always increase innovation in the teaching process and increase interest in literacy.